2015
DOI: 10.2500/ajra.2015.29.4210
|View full text |Cite
|
Sign up to set email alerts
|

Serum Indolamine 2,3 Dioxygenase as a Marker in the Evaluation of Allergic Rhinitis

Abstract: IDO plays an important role in patients with atopic symptomatic allergic rhinitis, especially with increased levels of IgE. There is no relationship between IDO levels and severity of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Several studies from our group reported a prevalence of 50–75% among non-atopic individuals with nasal symptoms suggestive of allergy [9,11,23,36]. Nevertheless, the existing literature reflects an extremely wide range of LAR prevalence among non-atopic rhinitis patients (0–100%) [9,21,22,23,24,26,27,28,29,30,31,32,33,34,37]. In recent years, several studies from Asian countries have become available and overall report a lower (<20%) prevalence of LAR as compared to Western countries [26,27,29,33,37].…”
Section: Epidemiologymentioning
confidence: 95%
See 1 more Smart Citation
“…Several studies from our group reported a prevalence of 50–75% among non-atopic individuals with nasal symptoms suggestive of allergy [9,11,23,36]. Nevertheless, the existing literature reflects an extremely wide range of LAR prevalence among non-atopic rhinitis patients (0–100%) [9,21,22,23,24,26,27,28,29,30,31,32,33,34,37]. In recent years, several studies from Asian countries have become available and overall report a lower (<20%) prevalence of LAR as compared to Western countries [26,27,29,33,37].…”
Section: Epidemiologymentioning
confidence: 95%
“…Although large population studies are lacking, different works report that LAR is an underdiagnosed entity, affecting a considerable proportion of non-atopic rhinitis individuals of different countries, ethnic backgrounds, and age ranges [9,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35]. Several studies from our group reported a prevalence of 50–75% among non-atopic individuals with nasal symptoms suggestive of allergy [9,11,23,36].…”
Section: Epidemiologymentioning
confidence: 99%
“…TNSS is the sum of four individual symptom scores (sneezing, rhinorrhea, nasal congestion, and nasal itching), and each symptom ranged from 0 to 3, resulting in a possible score of 0–12 (detailed described in Supplementary Table S1 ). Based on TNSS, AR patients were categorized into the mild AR (MAR) group (TNSS ≤4) and the moderate–severe AR (MSAR) group (TNSS >4) according to recommendation by previous publications ( Refaat et al, 2015 ; Adamko et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…16 Indolamine-2,3-dioxygenase is a metabolic enzyme induced by immune activation. Refaat et al 17 found a significant increase in indolamine-2,3-dioxygenase levels in allergic rhinitis compared with subjects without allergy. Indolamine-2,3-dioxygenase was positively correlated with total serum IgE levels.…”
Section: T His Issue Of American Journal Of Rhinology Andmentioning
confidence: 99%
“…Indolamine-2,3-dioxygenase was positively correlated with total serum IgE levels. 17 Choosing between skin-prick tests and in vitro blood tests to evaluate aeroallergen sensitivity in chronic rhinitis is an important decision. In a comprehensive review, Oppenheimer 18 discusses concerns and advantages of each test that can help clinicians make the right choice in various clinical scenarios.…”
Section: T His Issue Of American Journal Of Rhinology Andmentioning
confidence: 99%